2020
DOI: 10.3390/bs10060102
|View full text |Cite
|
Sign up to set email alerts
|

Child Wantedness and Low Weight at Birth: Differential Parental Investment among Roma

Abstract: Studies investigating child wantedness, birthweight and parental care are limited. This study assessed relationships of child wantedness, low birthweight and differential parental investment in a poor population of Serbian Roma. Data from the Multiple Indicator Cluster Survey round 5 for Roma settlements were used to account for the association between child wantedness and birthweight, and three measures of parental investment: breastfeeding practices, immunization of children and quality of mother–child inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Early development of Roma children was positively influenced by maternal investment; across various studies, activities with children such as reading, singing and playing are consistently associated positively with language, cognitive and socio-emotional development (35) . As in other studies, overall parental investment was low but higher for mothers (30,74) and lowest for children born to mothers who married at 10-15 years of age, indicating that the overall investment received may be reduced in households with numerous children.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Early development of Roma children was positively influenced by maternal investment; across various studies, activities with children such as reading, singing and playing are consistently associated positively with language, cognitive and socio-emotional development (35) . As in other studies, overall parental investment was low but higher for mothers (30,74) and lowest for children born to mothers who married at 10-15 years of age, indicating that the overall investment received may be reduced in households with numerous children.…”
Section: Discussionsupporting
confidence: 74%
“…In this sample, the observed mean age at first marriage was 17, while the mean age at first reproduction was at an optimum of 18 years. Previous studies on the Roma reproductive pattern found that Roma women start reproducing at the optimum age, continue having children in their most fertile years and cease reproduction relatively early, with later age at first reproduction being significantly associated with infant low birth weight (20,30) . The risks associated with later maternal age at first reproduction include changes in children's quantity but also quality, suggesting a significant disadvantage of delayed age at first reproduction (21,(42)(43)(44) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations